production of Trichoderma reesei cellulase and enzymatic hydrolysis of lignocellulosic materials for chemical feedstock -production - Stener, W. (Serdang, Selangor (Malaysia), 2013)
Cellulase was produced by cultivating Trichoderma reesi strains (QM 9414.MCG 77) on spruce sulfite pulp in both laboratory fermentors and pilot fermentors. The culture broth contained 3-5 filter paper units/ml (FPU/ml) depending on the fermentation parameters. The solid enzyme prepared by solvent precipitation contained 96% protein and 0.73 FPU/mg. 0.35 units B-glucosidase/mg and 9.8 units xylanase/mg. Analytical chromatofocusing was used to further characterize the individual protein constituents of the cellulase preparations. This method appears useful for defining the enzyme quality. The T. reesi culture broth freed from the mycelia was used to saccharify (10 FPU/g, 50 deg C, pH 4.8) waste paper and cereal straws. Untreated materials gave only low sugar yields. Treatment of waste paper with refiners increased the sugar yield to maximal 66% of the theoretical value (66.6 g sugar/100 g dry matter). Milling was not effective in the case of wheat straw. The saccharification of this material, was nearly quantitative (74 g sugars/100 g dry matter) if it was pretreated by a thermal process. The paper also reports on the present status of research and development in the cellulase field in Austria, the available pilot facilities and the experiences in the pilot studies